Transcriptome analyses reveal the flowering regulatory networks in the desert ephemeral plant Eremopyrum triticeum - Zeng, Ling-Lu; Meng, Wan-Qiu; Zhong, Xue-Ni; Peng, Jun-Jie; Yang, Xiu-Li; Sun, Li (Frontiers in Plant Science, 2025)
Eremopyrum triticeum, an annual spring ephemeral plant and a wild relative of wheat (Triticum aestivum), is widely distributed in the Junggar Desert of northern Xinjiang, China. It has several adaptive traits to survive in the desert environments, such as rapid growth in the early spring, flowers quickly, and completes its life cycle within approximately two months. However, the adaptation mechanisms of the fast flowering are still unknown. In this study, high-throughput RNA sequencing (RNA-seq) was performed to identify differentially expressed genes (DEGs) associated with flowering in E. triticeum during three developmental stages. A total of 11,278 DEGs were identified, including 1,632 DEGs specifically expressed during the flowering stage. Pathway analysis showed that these DEGs are mainly enriched in plant-pathogen interaction, plant hormone signal transduction, the MAPK signaling pathway, and so on. A total of 92 DEGs related to the flowering pathway were identified, which are mainly involved in the photoperiod, hormone signaling, autonomous, and vernalization pathway. Multiple transcription factor families related to floral transition were identified, with members of the MADS-box, bHLH, MYB, and AP2 families being the most abundant. In addition, four FLOWERING LOCUS T (FT) genes were identified in E. triticeum, and three of them were highly up-regulated at the flowering stage. The expression of EtFT-1 was induced in darkness, and short-day conditions promote its expression. Overexpression of the EtFT-1 gene accelerates flowering in Arabidopsis.